Toward the Development of Key Competencies: A Conceptual Framework for the STEM Curriculum Design and a Case Study - Hu, Weiping; Guo, Xipei (Frontiers in Education, 2021)
National attention has been given to science, technology, engineering, and mathematics (STEM) education, which is well recognized as an effective way to cultivate the key competencies of 21st-century talents. However, current STEM education falls short of the desired results. The fundamental reason is that there has not been a clearly and structurally explained systematic construction and effective implementation of STEM curricula. Accordingly, this article systematically expounds on the construction of the STEM curricula system from four aspects. Specifically, we first proposed the components of the STEM competencies as the goal of STEM education to provide a guiding direction for other parts of the design of the STEM curricula. Then, we elaborated on how to cultivate the STEM competencies from two aspects: the design principles of the STEM curricula content and the implementation strategies of STEM teaching. Finally, we explained how to effectively evaluate to monitor and improve the implementation of the STEM curriculum. In addition to the above mentioned, we then presented a case study of STEM courses constructed under the guidance of “think-based instruction theory” (TBIT) to help readers further understand the nature of the STEM curricula.